1994
DOI: 10.1108/01443579410056795
|View full text |Cite
|
Sign up to set email alerts
|

Improving Service: Managing Response Time in Hospitality Operations

Abstract: Investigates customer attitudes to waiting times in the hotel and restaurant industry, based broadly on Maister′s “psychology of waiting lines”. Results of a survey of 100 customers suggest that customer behaviour is affected by the length of time they have to wait. Also investigates the response times found in typical hotel and restaurant operations managed by Forte plc. Comparison is made between customer attitudes and the firm′s ability to deliver. On the basis of this the company developed ten key action p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 4 publications
2
31
0
Order By: Relevance
“…Others also ventured for fast service for the business customer. This supported the view that response time is important in service delivery since it affects customer satisfaction and behavioural intentions (Jones & Dent, 1994). Service speed could affect customer experiences, where delays contribute to unfavourable experiences.…”
Section: Wwwccsenetorg/ijmssupporting
confidence: 57%
See 1 more Smart Citation
“…Others also ventured for fast service for the business customer. This supported the view that response time is important in service delivery since it affects customer satisfaction and behavioural intentions (Jones & Dent, 1994). Service speed could affect customer experiences, where delays contribute to unfavourable experiences.…”
Section: Wwwccsenetorg/ijmssupporting
confidence: 57%
“…Service speed could affect customer experiences, where delays contribute to unfavourable experiences. Jones and Dent (1994) emphasised that service speed mattered during arrival, seating, ordering, serving food and drinks and during payment while at the front desk, service delivery speed was important during check-in, check-out, porterage, use of telephone, message delivery and when providing room service. However, an exception to this approach to service can be found in luxurious hotels where the customer accepts slow personalised service which is part of the meal experience and which is done in order to increase the average spend by the guest and justify the high prices charged, as is seen with gueridon service and elite guests (Goodman, 1996).…”
Section: Wwwccsenetorg/ijmsmentioning
confidence: 99%
“…However, Houston et al (1998) argued that the perceived wait duration approach was only half the story and suggested that attributions about the cause of the wait would also be needed. In a study with restaurant customers, Jones and Dent (1994) found that a smiling face and an apology to customers made waiting more bearable. This dual intervention perspective is pursued further with the focus on how the customer attributed the intervention.…”
Section: Waiting For Servicementioning
confidence: 97%
“…Punctuality and valence are two dimensions of outcome quality developed by Caro and Roemer (2006). However, some factors, such as valence, sociability, and waiting time, are suggested by several studies García, 2007, 2008;Caro and Roemer, 2006;Brady and Cronin, 2001;Jones and Dent, 1994;Ko and Pastore, 2005;Wu and Ko, 2013).…”
Section: Outcome Qualitymentioning
confidence: 99%